Characterization of the magnetic Fe₃O₄ nanoparticles prepared by gamma irradiation - Tran , Minh Quynh; Nguyen , Van Binh; Nguyen , Quang Long; Hoang , Dang Sang (Nuclear Science and Technology, 2014)
In this study, gamma irradiation treatment has been applied for preparation of the magnetic nanoparticles from iron(III) chloride (FeCl3). Structure of the resulting black powders were characterized with X-ray diffraction (XRD). The results revealed that the products prepared by gamma irradiation were mainly magnetite (Fe3O4) instead of maghemite (Fe2O3). The basic characteristics of the magnetite nanoparticles such as their particle size and magnetic properties were investigated using scanning electron microscope (SEM) and vibrating sample magnetometer (VSM). The nanoparticles showed superparamagnetism with the saturated magnetization of about 48.6 emu/g. Influences of radiation conditions on radiation preparation of magnetite nanoparticles and their properties were also discussed. Reaction yield increased, while average diameter of the obtained nanoparticles reduced from 46 to 17 nm depended on the absorbed dose